Dental management of PHACE syndrome under general anesthesia - S Fernandes; A Kakade; A M Jetpurwala; B Patil; S Jain; P Kasar (Wolters Kluwer Medknow Publications, 2011)
PHACE syndrome was first described by Dr. Ilonia Frieden and colleagues in 1996. It is an under-recognized rather than a very rare condition among patients with large facial hemangiomas. It is challenging as it has significant neurological, vascular and airway implications. Vascular malformations compromising cerebral blood flow predispose the patient to strokes and seizures. Subglottic hemangiomas, if present, could bleed during intubation. Meticulous neurological monitoring is mandatory in those undergoing repair of the great vessels. We describe the perioperative management of a child with PHACE syndrome subjected to dental treatment under general anesthesia.